The impact of creditor rights on commercial bank capital ratios: Evidence from the European Union - FAN, GE (2020)
This paper examines the influence of creditor rights on bank capital ratios for EU countries from 709 commercial banks over the 2012-2018 period. I construct an empirical model using the OLS approach as baseline regression to investigate the relationship between the independent variable (creditor rights) and dependent variables (TCR and EQTA). The results show that stronger creditor rights promote the increase in bank capital ratios. Furthermore, I regress the model with random effects and instrumental variable methods to confirm the robustness of my baseline results. Moreover, I add a new variable deposit insurance coverage to test robustness. The results show that creditor rights still have a positive and significant impact on bank capital ratios when there is a deposit insurance scheme. Also, I split my sample into large or small bank sizes and high or low risk-shifting countries. For large-size banks, the influence of creditor rights on the capital adequacy ratio is significant. For high risk-shifting countries, banks are accompanied by high-risk exposure, suggesting that strong creditor rights and banks in high risk-shifting countries may increase capital adequacy ratio. Key words: creditor rights, bank capital ratios, deposit insurance, market discipline